Root hydraulic conductance, gas exchange and leaf water potential in seedlings of Pistacia lentiscus L. and Quercus suber L. grown under different fertilization and light regimes - Hernández, E I; Vilagrosa, A; Luis, V C; Llorca, M; Chirino, E; Vallejo, V R (Environmental and Experimental Botany, 2009)
Differences in morphology, biomass allocations and physiological responses were investigated in seedlings of Mastic tree (Pistacia lentiscus L.) and Cork oak (Quercus suber L.) submitted to contrasting fertilization and light regimes during early growth. These species are two evergreen sclerophyllous Mediterranean species frequently used in Mediterranean reforestation programmes. Fertilization was the treatment that affected most of the morphological and physiological variables evaluated in P. lentiscus and Q. suber seedlings. Leaf area and speciﬁc leaf area (SLA) were affected by shading treatment in both species, showing higher values in seedlings grown under shade. P. lentiscus seedlings showed a high capacity to modify root morphological variables and root hydraulic conductance (KR) with the fertilization treatment. In contrast, Q. suber showed low to moderate root system changes with the treatments applied, although the fertilization level affected biomass allocation (i.e., root to shoot ratio) in both species. Under high water demand, P. lentiscus seedlings with high KR allowed transpiration (E) to increase without increasing the water potential gradient between soil and leaves. In Q. suber, high fertilization induced signiﬁcant increases in photosynthesis (A), as well as a tendency to increase E with signiﬁcantly lower leaf water potential ( L)
Keywords: Drought; fertilization; Gas exchange; light; Root hydraulic conductance

Effects of a deep container on morpho-functional characteristics and root colonization in Quercus suber L. seedlings for reforestation in Mediterranean climate - Chirino, E; Vilagrosa, A; Hernández, E I; Matos, A; Vallejo, V R (Forest Ecology and Management, 2008)
In the last decades, reforestation and afforestation programs are being carried out mainly with containerized seedlings. Container design determines the morphological and physiological characteristics of seedlings. However, container characteristics are often the same for plant species with very different growth strategies. The most commonly used nursery containers are relatively shallow and limit tap root growth; consequently, species relying on the early development of a long tap root to escape drought, such as those of the Quercus genus, might need to be cultivated in deep containers. The aim of this paper was to compare the morphological and physiological characteristics of Quercus suber L. seedlings cultivated in shallow containers (CCS-18, depth 18 cm) with seedlings cultivated in deep containers (CCL-30, depth 30 cm). Both container types used were made of high-density polyethylene, cylindrical in shape, open-bottomed, with a diameter of 5 cm, two kinds of vertical ribs on the inside wall showing a cultivation density of 318 seedlings/m2 . At the end of nursery culture, the seedlings cultivated in the CCL-30 deep container presented a longer tap root, higher shoot and root biomass and higher Dickson Quality Index (DQI). Moreover, the CCL-30 seedlings showed a higher root growth capacity (RGC), they reached deep substrate layers faster and they presented higher root hydraulic conductance. These morpho-functional advantages improved the CCL-30 seedling water status, which was expressed by higher stomatal conductance during an imposed drought period
Keywords: Forest tray; Hydraulic conductance; root system; Stomatal conductance